2008
DOI: 10.1007/s12016-008-8082-1
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Cystic Fibrosis

Abstract: Newborn screening (NBS) for cystic fibrosis (CF) has evolved considerably from its beginnings. We review the early history of NBS in the USA and the evolution of CF NBS from its conception in observational studies, to the development of mass-screening methodology in the 1970s, and to its early applications in the USA and other countries. We review the development of current CF NBS algorithms, particularly the development of those used in the Wisconsin randomized controlled trial, and discuss the comparative ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Wide differences in allele frequencies may also contribute to differences in disease prevalence between racial groups. For instance the cystic fibrosis has large racial disparities [35] and as expected we found large differences in the CFTR gene (rs213950) among different racial groups in our population.…”
Section: Discussionsupporting
confidence: 83%
“…Wide differences in allele frequencies may also contribute to differences in disease prevalence between racial groups. For instance the cystic fibrosis has large racial disparities [35] and as expected we found large differences in the CFTR gene (rs213950) among different racial groups in our population.…”
Section: Discussionsupporting
confidence: 83%
“…Sharp and Rock 55 showed that screening for CF has a significant impact on lung growth and function, and that early intervention (within the first 2 months of life) may be a critical time to make the diagnosis and begin therapies for CF. Because the average CF diagnosis occurs in the fourth year of life in Brazil, 34 nutritional development and pulmonary function of patients are often compromised.…”
Section: Resultsmentioning
confidence: 99%
“…This method can detect most infants with CF, both pancreatic insufficient and sufficient, and two dosages of elevated IRT is needed to carry out the CF diagnosis. 55 Currently, PR screens for CF using the IRT/IRT protocol, and the analysis of the p.F508del mutation is being carried out only for research purposes. It is apparent that in other states, such as BA, the use of this mutation for the screening of CF may be useful only if a panel of 40 mutations is included in the test.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been an increase in the number of CF screening programs around the world (9). However, newborn screening for CF has been hotly debated because of the lack of a definitive test for CF screening (15) and some concerns about the long-term benefits of these programs (10,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Newborn screening for CF is expanding rapidly both in the US and in many European countries (9,10). In Brazil, only 3 of the 27 states have programs for CF screening.…”
mentioning
confidence: 99%